Educational proposals for preventing elder abuse adults through gamification: action research. - Vernasque, Juliana Ribeiro da Silva; Alarcon, Miriam Fernanda Sanches; Rodrigues, Paula Sales; Gimenez, Fabiana Veronez Martelato; Silva, Maria; Sanches Marin, Maria José de Lourdes da (Anna Nery School Journal of Nursing / Escola Anna Nery Revista de Enfermagem, 2025)
Objective: to develop gamified educational proposals to prevent elder abuse, engaging college students from different fields of knowledge, and to assess their attitudes, perceptions, and knowledge of gamification. Method: critical-collaborative action research was conducted in a municipality in the countryside of São Paulo, between December 2022 and December 2023, with health, humanities, and exact students. Forty participants were organized into groups guided by a game design specialist and researchers. Initially, they received training on gamification and elder abuse. Throughout the process, successive assessments and self-assessments were carried out by 22 students who remained until the end of the activities. Results: six gamified proposals addressing elder abuse prevention were developed, targeting different age groups and game modalities. Students reported significant changes in their attitudes, as well as an expansion of skills, and knowledge related to gamification. Conclusions and implications for practice: the collaborative development of gamified educational proposals proved to be an appropriate strategy to raise awareness about elder abuse prevention in diverse contexts, in addition to providing resources that can be applied by nurses to enhance professional practice.